Inisiasi Menyusu Dini (IMD) Mempengaruhi Involusi Uterus Pada Ibu Post Partum - Ririn Ramadhani Ridwan; Mona Nulanda; Rachmat Faisal Syamsu; Erlin Syahril (Wal'afiat Hospital Journal, 2021)
Early Initiation of Breastfeeding in the first hour after giving birth is the easiest and most successful breastfeeding effort, because in the first hour of delivery the mother is physically and psychologically ready to breastfeed, supported by information/counseling on breastfeeding and support from health service providers. Early initiation of breastfeeding is a factor that can accelerate the process of uterine involution. This is because the baby's sucking on the breast is continued through the nerves to the pituitary gland in the brain which secretes the hormone oxytocin. The presence of the baby's sucking on the mother's nipple causes more oxytocin to come out. One of the functions of oxytocin is to stimulate contraction of the smooth muscles of the uterus so that the uterine involution process can take place more quickly. The purpose of the literature review is to determine the effect of Early Initiation of Breastfeeding (IMD) on Uterine Involution in Post Partum Mothers. This study uses a narrative review method and data collection is carried out from several kinds of literature. The results of a narrative review of the literature found that there was an effect of early initiation of breastfeeding (IMD) on uterine involution. Research suggestions are expected to need further studies on other indicators that affect uterine involution in postpartum mothers.